DETERMINATION OF EVCS RATES IN THE AIRPORT AREA & ELECTRICITY SYSTEM ANALYSIS OF THE IMPACT OF ADDITIONAL EVCS LOADS AT SOEKARNO-HATTA INTERNATIONAL AIRPORT, TANGERANG BANTEN - Dwi Peanus, Arian
Utilize alternate forms of transportation, such as electric cars, to achieve cleaner energy, better air quality, fewer petrol emissions, and a more environmentally friendly atmosphere. This is expected to protect endurance energy while reducing fuel oil use. By installing vehicle charging facilities in public areas such as airports, it is hoped that this will encourage an increase in the population of electric vehicles.